2022
DOI: 10.4269/ajtmh.21-0614
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Shewanella Algae Pneumonia and Bacteremia in an Elderly Male Living at a Long-Term Care Facility

Abstract: Shewanella algae is a gram-negative, nonfermenting, oxidase-positive, motile bacillus that is ubiquitous in aquatic ecosystems. Human infections are rare and the immunocompromised are left most vulnerable. Risk factors for this infection include exposure to seawater, consumption of raw seafood, and underlying comorbid conditions such as hepatobiliary disease and chronic cutaneous ulcers. Previously documented cases of S. algae have involved near drownings, contaminated raw shellfish, or wound exposure to seawa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…[5,6] Other types of infections are rarely reported, and most cases occur in coastal areas or in individuals exposed to seawater and seafood. [7] Studies have identified several risk factors associated with Shewanella algae infection, including liver and bile diseases, chronic kidney disease, diabetes, malignant tumors, immune deficiency, chronic lower limb ulcers, and male gender, among others. [6,[8][9][10] After obtaining the identification results, the patient's medical history was reviewed, and it was discovered that the patient had a history of raw shrimp consumption prior to disease onset.…”
Section: Discussionmentioning
confidence: 99%
“…[5,6] Other types of infections are rarely reported, and most cases occur in coastal areas or in individuals exposed to seawater and seafood. [7] Studies have identified several risk factors associated with Shewanella algae infection, including liver and bile diseases, chronic kidney disease, diabetes, malignant tumors, immune deficiency, chronic lower limb ulcers, and male gender, among others. [6,[8][9][10] After obtaining the identification results, the patient's medical history was reviewed, and it was discovered that the patient had a history of raw shrimp consumption prior to disease onset.…”
Section: Discussionmentioning
confidence: 99%
“…Shewanella algae is primarily known as an opportunistic pathogen that commonly causes skin and soft tissue infections, followed by bloodstream infections and biliary tract infections [3][4]. Other types of infections are rarely reported, and most cases occur in coastal areas or in individuals who have been exposed to seawater and seafood [5]. Studies have identi ed several risk factors associated with Shewanella algae infection, including liver and bile diseases, chronic kidney disease, diabetes, malignant tumors, immune de ciency, chronic lower limb ulcers, and male gender, among others [4][6] [7][8].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review in Spain, unambiguous exposure to water was reported in the minority of cases and nosocomial infection was suspected [ 4 ]. Conditions affecting the immune response such as malnutrition, anemia, renal failure, diabetes, cancer, and liver cirrhosis seem to be more predisposed to Shewanella infections [ 10 ]. In our case, the patient did not have exposure to marine environment or seafood or fish but was immunocompromised, which is a risk factor for unusual infections.…”
Section: Discussionmentioning
confidence: 99%